Методологічні аспекти побудови інтелектуальних систем підтримки прийняття рішень в особливих ситуаціях - Андрощук, Олександр Степанович; Огурцов, Віталій Вячеславович; Демідова, Олена Іванівна (Eastern-European Journal of Enterprise Technologies, 2009)
In the article the theoretical aspects of the functional scheme’s construction and the groundwork of the intellectual systems of the decision-making support are scrutinized. They are discovered by means of the complex application of the mathematical methods at the solving of the problems in the various spheres of an activity.